Censuses in Peru - Solís Fonseca, Gustavo (1998)
In 1993, two censuses were carried out in Peru, the IX population census of recent times and the IV housing census. A new census has already been announced for 2001, this time a more complex one. Censuses are important for societies, but it is convenient to analyze their rationality in order to see how much we should expect from them, and how much it is licit to assign them in the account of responsibilities for how little or how much the censuses have served us so far.